Religião, redes sociais e capital social no Município de Rio Grande da Serra na Região do Grande ABC Paulista. Estudo das trocas materiais e simbólicas em contexto de periferia urbana - Noronha, Claudio Pereira (2015)
The municipality of Rio Grande da Serra is situated in a region Grande ABC paulista - nationally recognized for its economic and industrial development and the political and trade union struggles. Paradoxically, configures, socially and geographically speaking, for a region of urban periphery. Fashion result as urbanization, in modern society, conforms the space in central and peripheral regions. Located on the road linking Santos to Mogi das Cruzes (XIX century) - village of Geribatiba - resulting from urban transformations occurred throughout the region, conquer, in the 1960s, its political and administrative autonomy. In the following decades witnessed intense population growth, a result of the migration process, mainly from Minas Gerais state and Northeast region of the country, which had the cities and industries of São Paulo and Greater ABC as a destination. This displacement of people, and networks formed in his around, contributed to the development of his religious field. Currently, with a population around of 46 000 inhabitants, has approximately 180 locations in religious ceremonies. In this context, the thesis analyzes the regiona integration - social, economic and religious - of Rio Grande da Serra, from comparative data with other municipalities, and discusses how the regionalism has contributed to its economic development. Performs characterization of urban peripheries, discussing aspects attached to them, such as segregation and social vulnerability. In this sense, the research enabled the identification of the socioeconomic profile (income and education) of participants of religious groups (Catholics, Evangelicals, Kardecists and followers of Umbanda), allowing also identify social inequalities within its territory, noting that certain neighborhoods are more vulnerable than others. Whereas this study examines the ability of social and religious networks, to increase the share capital of its participants, was conducted mapping and ethnography of the various associative practices, more or less formal and structured, to analyze the material and symbolic elements produced. It was found, based on the questionnaires, interviews and participant observation, that, from the religious habitus of each group, the networks allow under economic issues such as employment and income or assistance in basic survival needs through campaigns and social work. In the symbolic context, networks provide important questions of human existence, such as the belief in salvation or soul evolution, socialization, self-esteem, prestige or the expectation of cure or treatment of chemical dependency. It was possible to ascertain that, despite the different ways in each group, and its participants, appropriate the social capital, social and religious networks in the city, function as safety nets, especially in high population situation of social vulnerability.